Hypoxia and Reoxygenation Induce Endothelial Nitric Oxide Synthase Uncoupling in Endothelial Cells through Tetrahydrobiopterin Depletion and S-Glutathionylation - De Pascali, Francesco (American Chemical Society, 2014)
[Image: see text] Ischemia-reperfusion injury is accompanied by endothelial hypoxia and reoxygenation that trigger oxidative stress with enhanced superoxide generation and diminished nitric oxide (NO) production leading to endothelial dysfunction. Oxidative depletion of the endothelial NO synthase (eNOS) cofactor tetrahydrobiopterin can trigger eNOS uncoupling, in which the enzyme generates superoxide rather than NO. Recently, it has also been shown that oxidative stress can induce eNOS S-glutathionylation at critical cysteine residues of the reductase site that serves as a redox switch to control eNOS coupling. While superoxide can deplete tetrahydrobiopterin and induce eNOS S-glutathionylation, the extent of and interaction between these processes in the pathogenesis of eNOS dysfunction in endothelial cells following hypoxia and reoxygenation remain unknown. Therefore, studies were performed on endothelial cells subjected to hypoxia and reoxygenation to determine the severity of eNOS uncoupling and the role of cofactor depletion and S-glutathionylation in this process. Hypoxia and reoxygenation of aortic endothelial cells triggered xanthine oxidase-mediated superoxide generation, causing both tetrahydrobiopterin depletion and S-glutathionylation with resultant eNOS uncoupling. Replenishing cells with tetrahydrobiopterin along with increasing intracellular levels of glutathione greatly preserved eNOS activity after hypoxia and reoxygenation, while targeting either mechanism alone only partially ameliorated the decrease in NO. Endothelial oxidative stress, secondary to hypoxia and reoxygenation, uncoupled eNOS with an altered ratio of oxidized to reduced glutathione inducing eNOS S-glutathionylation. These mechanisms triggered by oxidative stress combine to cause eNOS dysfunction with shift of the enzyme from NO to superoxide production. Thus, in endothelial reoxygenation injury, normalization of both tetrahydrobiopterin levels and the glutathione pool are needed for maximal restoration of eNOS function and NO generation.